Diet Compliance, Blood Glucose Levels, and Hospitalization Duration of Type II Diabetes Mellitus Patients with Hypertension Complications in the Pancaran Kasih General Hospital, Manado - Walalangi, Rivolta G. M.; Legi, Nonce N.; Ondang, Olivia; Tomastola, Yohanis A.; Harikedua, Vera T.; Pesak, Ellen; Ranti, Irza N.; Montol, Ana B.; Paruntu, Olga L.; Robert, Daniel; Sineke, Jufri; Kereh, Phembriah S.; et al. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUD: Diabetes mellitus is an assembly of symptoms that arise in a person caused by increased blood sugar levels due to insulin deficiency, both absolute and relative. The highest prevalence in North Sulawesi is in Tomohon City (4.8%) then Manado City (3.2%). AIM: This study aimed to determine the correlation between dietary compliance with blood glucose levels and duration of hospitalization of type 2 diabetes mellitus (T2DM) patients with hypertension complications in the Pancaran Kasih General Hospital, Manado. METHOD: This research was observational with a cross-sectional design. The population in this study were all patients with type 2 diabetes who were hospitalized and 34 people involved as a sample through purposive sampling technique. RESULTS: The results showed that 88.2% of respondents with not normal blood glucose did not adhere to the diet. Fisher’s test obtained p = 0.011 (p < 0.05), indicated a significant correlation between dietary compliance with blood glucose levels. About 82.4% of patients did not adhere to the diet with a long day of hospitalization and p = 0.027 (p < 0.05). It indicated a significant correlation between dietary compliance and length of stay. CONCLUSION: This study concluded a correlation between dietary compliance with blood glucose levels and dietary compliance and length of stay for T2DM patients with hypertension complications.